Humanistic Philosophy of Learning Differs From the Curriculum in ES - Halimah, Nurul; Irdamurni, Irdamurni; Desyandri, Desyandri (International Journal of Educational Dynamics, 2023)
This research aims to discuss the application of humanistic philosophy in differential learning to the Merdeka Curriculum in Elementary School (ES). The method used in this study is a library study or literature review. Data collection techniques are done by searching for articles, books, slides, and other information on the internet. Based on the results of research, it is known that humanistic philosophy emphasizes the appreciation of individual uniqueness, student empowerment, collaboration and communication, meaningful learning experiences, and lifelong learning. Differentiated learning recognizes the individual differences of students in abilities, interests, and learning styles. In the Merdeka Curriculum, a differentiated learning approach based on humanistic philosophy creates an inclusive environment in ES. Teachers understand the uniqueness of each student and design learning strategies that suit their needs. Students are empowered to take an active role in their learning, choose learning goals, and be responsible for their learning progress.